A review on the effects of various supplementary cementitious materials on physical properties of hardened concrete - Barbhuiya, Salim; Nikraz, Hamid (Trans Tech Publications, Switzerland, 2014)
The global development and current trends in social attitude are resulting in an increase in the amount of waste generated by society, the treatment and disposal of which are becoming a serious problem. Therefore, waste management is one of the most important aspects in ensuring sustainable development in today’s world. Some of the industrial by-products, such as pulverised-fuel ash (PFA), ground granulated blast-furnace slag (GGBS) and microsilica (MS) can be used in concrete to improve its properties. In this paper the influence of various by-products on the physical properties of concrete is reviewed.